(3GdNHQ GdUMaj (B:s (3GgejJg(B-(3JYQjag(B-(3GfhGYg(B-(3eUGOQg (B-(3ePGgH fTQg(B-(3WQb JMQjQg (B- (3TQMg h JaSjQg (B/s - (3NVhQ, COjHs ([(3Ohf ecGf(B] :s (3OGQ GdHYK ,s)
(3ehVhY gPG GdcJGH gh JYQja GdNHQ GdUMaj (B-(3cja fMQQGdNHQ GdUMaj(B- (3cja fVY GdYfhGf h eGgj GfhGg GdYfGhjf(B- (3cja JUHM ebOeI GdNHQ h eGgj GdGfhGY GdeNJdaI debOeI GdNHQ (B-(3cja JMQQMSe GdNHQ h eGgj GdWQb GdeNJdaI dUjGZI GdNHQ eGgj GfhGY GdGNHGQ (B-(3h eGgj GdePGgH GdeNJdaI dfTQ GdNHQ (B-(3eGgj Gdbje GdGNHGQjI (B-(3h cja fbjS GgejI GdNHQ (B-(3cja faSQ GdNHQ h cja fVY dg (B---(3jMGhd GdcJGH Gf jbOe GLGHI YdejI Ydi gPg GdGSFdI cGaI(B.s
Keywords: (3GdCNHGQs; (3GdNHQ GdUMajs; (3GdUMGaIs